Reliability and Validity of the Function Impairment Screening Tool in Chinese Older Adults - Zhang, Yaxin; Liu, Pan; Pan, Yiming; Li, Ying; Zhang, Li; Li, Yun; Ma, Lina (Frontiers in Medicine, 2021)
Background: Physical function gradually decreases with age in older adults, affecting their independence and quality of life and leaving them prone to adverse outcomes. Despite the importance of assessing function for older adults, most studies have focused on disability and paid less attention to functional impairment. Thus, given the lack of valid and practical methods for evaluating functional impairment for older adults, we developed the function impairment screening tool (FIST) using the Delphi method. Objective: This study aimed to evaluate the reliability and validity of the FIST in Chinese older adults. Methods: A total of 489 participants aged 60 years or older, and who had completed the FIST were included. A subgroup of 50 participants completed the FIST a second time, one week after the first round, and the test-retest reliability was evaluated using the intraclass correlation coefficient (ICC). Reliability was tested using Cronbach’s alpha. Validity was examined using exploratory factor analysis. Criterion-related validity was assessed using correlations between the FIST and the Barthel Index activities of daily living (ADL), Lawton and Brody instrumental activities of daily living (LB-IADL). Results: The Cronbach’s alpha coefficient for the FIST was 0.930 (P ＜0.001). The test-retest reliability was good, with an ICC of 0.928 (95% confidence interval [0.874, 0.960]). Exploratory factor analyses revealed one factor accounting for 60.14% of the scale’s variance and the load values of every item were ＞0.2 (0.489–0.872). The correlated coefficient for the FIST score and ADL was 0.572 (P ＜ 0.001). That between the FIST score and IADL was 0.793 (P ＜ 0.001). The FIST score was positively correlated with walking speed (r = 0.475, P ＜ 0.001) and grip strength (r = 0.307, P ＜ 0.001), and negatively correlated with age (r = -0.588, P＜ 0.001) and Fried frailty phenotype (r = -0.594, P ＜ 0.001). Conclusion: The FIST is a reliable and valid instrument for assessing physical function impairment in older adults.